2010
DOI: 10.1186/1742-7622-7-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two approaches for measuring household wealth via an asset-based index in rural and peri-urban settings of Hunan province, China

Abstract: BackgroundThere are growing concerns regarding inequities in health, with poverty being an important determinant of health as well as a product of health status. Within the People's Republic of China (P.R. China), disparities in socio-economic position are apparent, with the rural-urban gap of particular concern. Our aim was to compare direct and proxy methods of estimating household wealth in a rural and a peri-urban setting of Hunan province, P.R. China.MethodsWe collected data on ownership of household dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 42 publications
4
50
0
5
Order By: Relevance
“…Earlier socio-economic measurement approaches dwelt on money metric measures such as the Gini coefficient, Purchasing Power Parity and gross domestic product (GDP) per capita. These so-called "direct" measures of socio-economic status (The World Bank, 2004;Balen et al, 2010) are heavily based on income, consumption and financial assets such as savings and pensions.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier socio-economic measurement approaches dwelt on money metric measures such as the Gini coefficient, Purchasing Power Parity and gross domestic product (GDP) per capita. These so-called "direct" measures of socio-economic status (The World Bank, 2004;Balen et al, 2010) are heavily based on income, consumption and financial assets such as savings and pensions.…”
Section: Introductionmentioning
confidence: 99%
“…Poverty is a key social determinant of schistosomiasis [24][26], [38], [41], [42], [61]. We found that patients with advanced schistosomiasis were among the poorest individuals in the community.…”
Section: Discussionmentioning
confidence: 76%
“…Sustainability of local strategies towards interrupting schistosomiasis transmission elimination also requires improving sanitation by supplying clean drinking water and improving WASH approach in remote rural communities/ dwellings including intensive health education a continuous awareness and resilience [2,15,29,[93][94][95]. Moreover, to nurture schistosomiasis ownership and reinforcement of public-private partnership and collaboration including the local community in sustained funding support from government and international organizations and development of disease resilience culture are proactive and efficient ways in revamping the persistent morbidity and mortality of this diseases China and mainly in sub-Saharan Africa [3,5,19,96,[99][100][101][102].…”
Section: Impact Evaluation Of Schistosomiasis Control Models and Stramentioning
confidence: 99%